Playroom : AN INVESTIGATION OF THE POSSIBILITIES OF INTERDISCIPLINARY ACTIONS IN THE FORMATION OF PEDAGOGUES (Interdisciplinary Studies Journal, 2021)
In this text, we present a study aimed at investigating the space and time of the toy library as a research laboratory on play, games, and recreational activities, connected to educational processes in Pedagogy courses. This theme is justified as it is necessary to deepen the concept of the toy library as a scientific learning space, with tools that enable the enhancement of the concept of play, games, and recreational activities in the training of pedagogues for their future work in Early Childhood Education and the early grades of Elementary School. Methodologically, in the qualitative research conducted at a public University’s Faculty of Education, the action-research methodology was used, with students and professors from the faculty who volunteered to participate. Initially, a Study Group was formed with the students, with the objective of not only collectively developing studies for a theoretical deepening on the theme but also developing, in the toy library space, experimental activities in the form of workshops and playful activities, aiming to deepen, from a practical point of view, the readings on the toy library in the pedagogical training. Professors also participated as subjects of the research by answering a questionnaire that investigated other possibilities for actions in the toy library, connected to the course subjects. As research results, various theoretical arguments were found, also supported by responses to the questionnaire, backing the idea of the toy library as a laboratory of significant importance in the educator's formation. However, many weaknesses were still detected in the implementation of practices that could, in fact, legitimize this space in teacher formation, establishing the permanent use of the toy library as a laboratory for scientific and interdisciplinary actions, as required by such training.
Keywords: Toy Library; Play; Games; Recreational Activities; Teacher Training